Kepemimpinan Melayani Visi dan Misi dalam Perspektif Kristen - Heki Saogo; Seriya Seriya; Semuel Linggi Topayung (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
Service-based leadership is a leadership approach that prioritizes devotion to others as the center of a leader's function. In the Christian view, this model is rooted in the example set by Jesus Christ who came to serve, not to be served (Mark 10:45). The concept of servant leadership emphasizes values such as simplicity, love, sacrifice, and moral responsibility towards those being led. This study aims to explore how servant leadership influences and shapes the formulation of vision and mission in the context of Christian organizations or ministries. Vision and mission not only function as strategic guidelines, but also reflect the calling and obedience to God's will. A Christian leader who adopts the principle of servant leadership will create a vision that focuses on the common good, spiritual growth, and empowerment of community members. Meanwhile, the mission is designed to manifest the love of Christ in real terms through actions and programs that have a broad impact. In this context, sensitivity to the leadership of the Holy Spirit, integrity in leadership, and the ability to motivate and support the development of others are needed. This study concludes that servant leadership from a Christian perspective not only functions well in organizations, but also strengthens the spirituality and unity of the body of Christ. Therefore, the formulation of the vision and mission resulting from the principle of serving not only reflects the direction, but also becomes a testimony of faith that lives in the community. Thus, servant leadership becomes a strong foundation in building a Christian organization that is relevant, impactful, and oriented towards the values of the kingdom of God, and is able to answer the challenges of the times with love, exemplary behavior, and sincere devotion and glorify God in service.